2021
DOI: 10.21608/eajbsa.2021.160456
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Histological Alterations in The Larvae of Culex pipiens L. (Diptera: Culicidae) Induced by Imidcaloproid and Tannic Acid

Abstract: and internal organelles. Both IMI and tannic acid showed nearly the same effect on the larvae histology. Based on these results, tested compounds could be used in the Integrated Pest Management (IPM) programs for greater effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other compounds such as tannins and saponins can reduce organisms' growth rate, affect feed efficiency and protein digestibility, and degrade their intestinal cells of them [23] . In a study carried out by Farahat et al [24] , a delay in the larval development of Culex pipiens L. mosquitoes (Diptera: Culicidae) subjected to treatment with tannic acids was observed, which suggests the effectiveness of these compounds in controlling insect pests. In addition to the secondary compounds of chili pepper extract, other factors can act on the performance of insect pests, such as the extract extraction methodology, the extracted plant part, and the vegetative stage of the plant.…”
Section: Resultsmentioning
confidence: 97%
“…Other compounds such as tannins and saponins can reduce organisms' growth rate, affect feed efficiency and protein digestibility, and degrade their intestinal cells of them [23] . In a study carried out by Farahat et al [24] , a delay in the larval development of Culex pipiens L. mosquitoes (Diptera: Culicidae) subjected to treatment with tannic acids was observed, which suggests the effectiveness of these compounds in controlling insect pests. In addition to the secondary compounds of chili pepper extract, other factors can act on the performance of insect pests, such as the extract extraction methodology, the extracted plant part, and the vegetative stage of the plant.…”
Section: Resultsmentioning
confidence: 97%
“…However, in our current study, the histological changes induced in the midgut of the 4 th larval instars of S. littoralis treated with imidacloprid was similar to these obtained by [52] for the midgut of Locusta migratoria treated with the same insecticide. Also, the histopathological alterations of imidacloprid and tannic acid on the larvae of Culex pipiens showed that the treated larvae had cytopathological alterations of the midgut epithelium, muscular layers, and epithelial cells [53].…”
Section: Discussionmentioning
confidence: 98%